2017
DOI: 10.1002/2016jb013612
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric delays in ground‐based GNSS multipath reflectometry—Experimental evidence from coastal sites

Abstract: Recent studies have demonstrated the utility of ground‐based Global Navigation Satellite Systems‐Multipath Reflectometry (GNSS‐MR) for sea level studies. Typical root‐mean‐square (RMS) differences of GNSS‐MR‐derived sea level time series with respect to nearby tide gauges are on the order of 6–40 cm, sufficiently accurate to estimate tidal and secular sea level variations but are possibly biased due to delay of the signal through the troposphere. In this study we investigate the tropospheric effect from more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 37 publications
4
65
0
1
Order By: Relevance
“…6 Standard deviation of the difference between the tide gauges and the Kalman filter solution as a function of time before evaluation for both GTGU and SPBY. Spectral analysis is possible after recording data from a sufficiently long satellite arc, i.e., roughly 20 min (Williams and Nievinski 2017). Least-squares inversion (LSQ) requires significantly more data, and thus, time before analysis is possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Standard deviation of the difference between the tide gauges and the Kalman filter solution as a function of time before evaluation for both GTGU and SPBY. Spectral analysis is possible after recording data from a sufficiently long satellite arc, i.e., roughly 20 min (Williams and Nievinski 2017). Least-squares inversion (LSQ) requires significantly more data, and thus, time before analysis is possible.…”
Section: Discussionmentioning
confidence: 99%
“…The data are taken from the GTGU installation at Onsala on day of year 357 in reflector height h . Depending on the height of the antenna above the reflecting surfaces, roughly 20 min of SNR data are enough for a single height retrieval (Williams and Nievinski 2017). This method, which we will refer to as spectral analysis, has been successfully demonstrated to be able to retrieve, for example, snow depth , where the assumption of a static reflector is appropriate.…”
Section: Current State Of Gnss Reflectometrymentioning
confidence: 99%
“…Due to the tropospheric delay, the measured reflector heights are always smaller than the true geometric heights. Williams and Nievinski (2017) demonstrated that ignoring the tropospheric delay in GNSS-IR induces a scale error in the reflector heights. We use a combination of astronomical…”
Section: Snr Data Analysismentioning
confidence: 99%
“…The complementary angle of the incidence angle ε defers from the elevation angle of the satellite due to the curvature of the reflecting surface and can be calculated according to [6,15]. The tropospheric refraction can be considered by a correction of ε derived from an astronomic refraction model [16][17][18][19].…”
Section: Analysis Of Snr Datamentioning
confidence: 99%